ANALISIS TINGKAT KEPUASAN MAHASISWA TERHADAP SISTEM INFORMASI KEUANGAN DAN AKADEMIK (SISKA) IIB DARMAJAYA - Winata, Andri; Nuansyah, Benny; Alfian, Firmansyah Yunialfi (Jurnal Manajemen Magister Darmajaya, 2017)
SISKA System is an advanced technology found in the college in order to facilitate students during study. The problem in this research was there were still many complaints from users about SISKA at IIB Darmajaya. The objective of this study is to analyze SISKA user satisfaction at IIB Darmajaya. The population in this study was all students in IIB Darmajaya as 19,410 students. The Sampling technique used was purposive sampling with respondent criteria of SISKA users in 2012-2015 as 100 respondents. The analysis tool was Importance Perfomance analysis (IPA).The analysis results with Importance Performance Analysis (IPA) showed that the level of system conformity of SISKA System is between 88.94% - 96.61%, which means that the level of conformity that existed at SISKA system was ranged quite good till very good. Based on the results of the Cartesian diagram obtained the following results: there were 3 attributes in A Quadrant, 6 attributes in B Quadrant, 3 Attributes in C Quadrant and 3 attributes in D Quadrant. Therefore, it can be concluded that student of SISKA users at IIB Darmajaya feel satisfied with the service from SISKA.Keywords : Students Satisfaction, Service Quality